Steady State Stability Analysis and Improvement using Eigenvalues and PSS: A Case Study of a Thermal Power Plant in Jamshoro, Pakistan - Shahani, Z. A.; Hashmani, A. A.; Shaikh, M. M. (Engineering, Technology & Applied Science Research, 2020)
The efficient handling and distribution of electrical power consist one of the most complex and appealing research problems. Due to the interconnection of different power plants and intensity of load, which gradually changes due to continuous change in load on generating units, careful treatment of the small disturbances in a power system which may lead to severe disturbance is necessary. Stability is an essential part in electrical power system operation and control. The stability problem is related with the behavior of synchronous machine after the power system is subjected to trouble. This work presents Steady State Stability (SSS) analysis of a Jamshoro Thermal Power Plant (JTPP) by using eigenvalue analysis of the different cases by varying load at three different positions. A mathematical model has been used for the JTPP with real data in order to examine the behavior of the system and to find the eigenvalues. A Simulink model of the JTTP for waveform analysis in MATLAB/Simulink has been used without and with Power System Stabilizer (PSS). Numerical quantification of the eigenvalues under the examined cases categorizes the stability of the system. The waveforms of the system are analyzed, and in cases of instability, the proposed procedure utilizing PSS helps in maintaining the system’s usual working conditions. The eigenvalue analysis and simulation results show the behavior of synchronous machines when loading changes gradually. The existing system becomes stable after more swings, whereas by using PSS in the existing system, stable regimes are attained in less time. The obtained results demonstrate the effectiveness of the proposed solution for SSS examination and securing of the disturbances of the JTPP.